Particle Becomes Energy = Energy Becomes Mass (Global Journal of Science Frontier Research, 2023)
Each and every living thing on planet earth consists of at least one or more cells in their structure as an organism A cell within each living thing has a chemical makeup that produces energy and is found in molecules that are supplied through its nutrition from the organism This is considered the cell s food source Energy is produced as the cell breaks down its nutritional source from the organism then the cell can perform functions that it generally carries out From the energy produced the cell has the ability to provide respiration create hormones enzymes and perform other functions that the cell carries out In energy transference a particle moves into a cell as the cell increases in mass it increases in density as density increases and particles accumulate in the cell the cell is forced to expand As the cell expands energy is created from the particles and energy is released When energy is created and released the cell divides into two cells then the process replicates itself as long as there are particles that are moving into the cell to create energy After the cell divides particles have lost their energy until new particles move into the cell and begin the process again For a particle to move into the cell a vacuum may be created to pull the particle to the cell For the particle to enter the cell Quantum tunneling must occur to penetrate the cell wall and enter the cell Quantum tunneling may occur through a wavelike effect which disrupts the cell wall for the particle to enter the cell The Schr dinger equation explains the waive function effects for Quantum Tunneling the Ti u equation explains the waive function effects of particles and temperature in thermodynamics in Quantum Biology and applying Einstein equation for energy mass and light for Quantum Mechanics
Keywords: life is quantum biology; tiȇu equation; particle becomes energy; energy becomes mass